Characteristics of student errors in solving geometric proof problems based on Newman's theory - Syifa Afidah Nurul Arifin; Iyon Maryono (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to determine the characteristics of student errors in solving geometry proof based on Newman's Theory. The research method used is a qualitative research method with a phenomenographic approach. This research was conducted to prevent students from repeating mistakes in advanced geometry courses. The types of errors based on Newman's Theory used in this study are: (1) reading errors in the representation of mathematical symbols; (2) comprehension errors of the proof problem; (3) transformation errors of the proof problem; (4) process skills errors of the proof problem; and (5) encoding errors. The subjects of this study were 15 students, and the instruments used were interview guidelines and documentation. The results of this study are reading errors in the representation of mathematical symbols with an average of 15.81%, with error characteristics that students do not write geometry symbols according to the rules. Comprehension errors of the proof problem with an average of 4.78%. Transformation errors of the proof problem with an average of 26.84%. Process skill errors of proof problems with an average of 29.04%. Encoding errors with an average of 23.53%.